Free Radical Scavenging Effect of Artocarpus kemando and Artocarpus odoratissimus: Structure-Activity Relationship of Flavonoid Derivatives - Ee, G.C.L.; Teo, S.H.; Go, R.; Lim, C.K.; Lim, Y.M.; Bong, C.F.J. (Asian Journal of Chemistry, 2011)
Antioxidant activities of extracts from Artocarpus kemando and Artocarpus odoratissimus and their pure chemical constituents (1-5) were investigated for their DPPH (2,2-diphenyl-1- picrylhydrazyl) free radical scavenging activities. The reduction of DPPH by the extracts from Artocarpus kemando gave promising results in the assays indicating that the extracts of Artocarpus kemando have high ability to act as free radical scavengers. Two compounds which are artosimmin and artomandin gave good activities while cycloartobiloxanthone indicated moderate activity. Hence, Artocarpus kemando may be considered a good source of natural antioxidant. However, all the extracts of Artocarpus odoratissimus exhibited weak inhibition activity (IC50 > 120 μg/ mL) against DPPH. This paper describes the structure-activity relationships of the compounds tested.